Science, Technology, Environment, and Medicine in Russia's Great War and Revolution, 1914-22 - Laĭus, I︠U︡. A. (I︠U︡lii︠a︡ Aleksandrovna); Palmer, Scott W., 1967-; Heywood, Anthony (Book collections on Project MUSE., 2022)
"This multi-author collection of sixteen essays examines a wide variety of topics related to developments in Russian science, technology, environmental policy, and medicine during the Great War and ensuing Civil War, c. 1914-1924"--